2010
DOI: 10.1186/1471-2164-11-235
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum spermidine synthase inhibition results in unique perturbation-specific effects observed on transcript, protein and metabolite levels

Abstract: BackgroundPlasmodium falciparum, the causative agent of severe human malaria, has evolved to become resistant to previously successful antimalarial chemotherapies, most notably chloroquine and the antifolates. The prevalence of resistant strains has necessitated the discovery and development of new chemical entities with novel modes-of-action. Although much effort has been invested in the creation of analogues based on existing drugs and the screening of chemical and natural compound libraries, a crucial short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Bacteria can either make their own polyamines (putrescine and spermidine) or import polyamines (spermidine, putrescine, and spermine) from the extracellular environment to grow (64). To identify mutants that were unable to utilize extracellular polyamines, we used an inhibitor of spermidine synthase, dicyclohexylamine (3,9,27,37,43). Isolates were selected from a library of mutants made with a Mariner-based transposon (50) that were unable to replicate in the presence of both the inhibitor and spermine in CDM.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria can either make their own polyamines (putrescine and spermidine) or import polyamines (spermidine, putrescine, and spermine) from the extracellular environment to grow (64). To identify mutants that were unable to utilize extracellular polyamines, we used an inhibitor of spermidine synthase, dicyclohexylamine (3,9,27,37,43). Isolates were selected from a library of mutants made with a Mariner-based transposon (50) that were unable to replicate in the presence of both the inhibitor and spermine in CDM.…”
Section: Resultsmentioning
confidence: 99%
“…RT-qPCR was performed on an Applied Biosystems 7500 Fast cycler (Carlsbad, California, USA) as described [26]. qPCR primers were designed using Primer3 Plus [27] and sequences are available on request.…”
Section: Methodsmentioning
confidence: 99%
“…showed that cyclohexylamine (a spermidine synthase inhibitor) treatment of P. falciparum resulted in transcriptional arrest of genes in the polyamine biosynthesis and associated metabolic pathways as well as differential expression of the corresponding proteins. Additionally, changes were observed in the levels of polyamine metabolites [56]. …”
Section: Metabolic Highlights Of Plasmodium Falciparummentioning
confidence: 99%